The rhetoric of risk: A critical discourse analysis of ’food fraud’ and public health - Mohamad, Omar Abu Al-Majd H. Q.; Namaziandost, Ehsan (Research Journal in Advanced Humanities, 2025)
The present study uses Critical Discourse Analysis (CDA) to examine the formulation and application of the term "food fraud" across academic, regulatory, and media contexts. We argue that the debate around food fraud goes beyond a technical definition and often focuses on economic and trade problems, which makes it more challenging to achieve a broad public health and sustainability aim. It also analyzes language, framing, and institutional power to demonstrate how the discourse of "fraud" characterizes criminality, obscures structural issues, and overlooks fundamental deficiencies within the food system. We contend that recontextualizing food fraud within the framework of the United Nations Sustainable Development Goals (SDGs)—specifically SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), SDG 12 (Responsible Consumption and Production), and SDG 16 (Peace, Justice, and Strong Institutions)—can elevate public health, environmental sustainability, and social equity in food safety governance.